Visible-Light-Induced Organocatalyzed [2+1] Cyclization of Alkynes and (Trifluoroacetyl)silanes - Zhou, Gang; Shen, Xiao (Synlett, 2022)
The synthesis of common cyclopropenes has been widely studied, but the synthesis of cyclopropenols is a significant challenge. Here, we highlight our recent work on the synthesis of trifluoromethylated cyclopropenols through a [2+1] cycloaddition reaction between alkynes and (trifluoroacetyl)silanes under visible-light-induced organocatalysis. The novel amphiphilic donor–acceptor carbenes derived from (trifluoroacetyl)silanes can react effectively with both activated and nonactivated alkynes. A broad substrate scope and a good functional-group tolerance have been achieved. Moreover, the synthetic potential of this reaction was highlighted by a gram-scale reaction and the one-pot diastereoselective synthesis of trifluoromethylated cyclopropanols.
Keywords: cyclopropenols; photocatalysis; organocatalysis; cyclopropanols; carbenes